Review of combine harvester losses for maize and influencing factors - Wang, Keru; Xie, Ruizhi; Ming, Bo; Hou, Peng; Xue, Jun; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2021)
The high harvest losses associated with the mechanical harvesting of maize in China are currently a major barrier to the adoption of this technology. This paper summarizes works of literature regarding harvest losses from the combine harvesting of maize in China and abroad. The main findings are as follows: (1) In 2012-2019, 2987 samples data obtained from the major maize production areas of China showed that the average harvest loss was 345.2 kg/hm2 (3.5% of the average yield), with losses ranging from 0 to 9288.5 kg/hm2; (2) The harvest losses from combine harvesting are mainly caused by the dropping of ears. The ear losses include the pre-harvest loss caused by ear abscission, damage caused by maize borer, lodging, and the ear loss during combine harvesting, and the main pre-harvest loss is caused by lodging; (3) Harvest losses are affected by maize variety, planting mode, cultivation management, pests and diseases, weather conditions during harvesting, harvest date, combine harvester type, harvester adjustment, operator proficiency, and the terrain conditions of the maize field; (4) The harvest losses from combine harvesting are also related to the type of header, feeding and threshing methods, the adjustment of header stripping clearance, feeding amount, forward speed, cylinder or rotor speed, and the clearance between the cylinder and the concave of the harvester. However, the combine losses mainly come from header losses. In order to reduce the harvest losses, the following solutions were proposed: (1) Breed and select maize varieties which are resistant to lodging, especially during the field drying of mature grains, as well as those resistant to maize borer and stalk rot; (2) Select varieties suitable for grain harvest—which requires matching the accumulated-temperature demand of the maize hybrids, optimal plant density, row spacing, and irrigation and fertilizer management with the light and heat conditions of the production area while cultivating uniform populations and healthy plants—as well as preventing and controlling damage from maize borer, stalk rot, and ear rot, harvesting at the appropriate time; (3) Develop and select advanced maize combine harvesters, formulate standardized operating procedures for harvesting machinery, and standardize field operation; (4) select appropriate agricultural machinery and agronomic practices, and improve the training of maize producers and harvester operators. Keywords: maize, grain, combine harvest, ear dropping, kernel dropping, harvest loss, influence factors DOI: 10.25165/j.ijabe.20211401.6034 Citation: Wang K R, Xie R Z, Ming B, Hou P, Xue J, Li S K. Review of combine harvester losses for maize and influencing factors. Int J Agric & Biol Eng, 2021; 14(1): 1–10.